Adult‐onset photosensitivity: clinical significance and epilepsy syndromes including idiopathic (possibly genetic) photosensitive occipital epilepsy. Issue 3 (1st October 2015) - Koutroumanidis, Michalis; Tsirka, Vasiliki; Panayiotopoulos, Chrysostomos
Abstract To evaluate the clinical associations of adult‐onset photosensitivity, we studied the clinical and EEG data of patients who were referred due to a possible first seizure and who had a photoparoxysmal response on their EEG. Patients with clinical evidence of photosensitivity before the age of 20 were excluded. Of a total of 30 patients, four had acute symptomatic seizures, two had vasovagal syncope, and 24 were diagnosed with epilepsy. Nine of the 24 patients had idiopathic (genetic) generalized epilepsies and predominantly generalized photoparoxysmal response, but also rare photically‐induced seizures, while 15 had exclusively, or almost exclusively, reflex photically‐induced occipital seizures with frequent secondary generalization and posterior photoparoxysmal response. Other important differences included a significantly older age at seizure onset and paucity of spontaneous interictal epileptic discharges in patients with photically‐induced occipital seizures; only a quarter of these had occasional occipital spikes, in contrast to the idiopathic (genetic) generalized epilepsy patients with typically generalized epileptic discharges. On the other hand, both groups shared a positive family history of epilepsy, common seizure threshold modulators (such as tiredness and sleep deprivation), normal neurological examination and MRI, a generally benign course, and good response to valproic acid. We demonstrated that photosensitivity can first occur in adult life and manifest, either as idiopathic (possibly genetic) photosensitive occipital epilepsy with secondary generalization or as an EEG, and less often, a clinical/EEG feature of idiopathic (genetic) generalized epilepsies. Identification of idiopathic photosensitive occipital epilepsy fills a diagnostic gap in adult first‐seizure epileptology and is clinically important because of its good response to antiepileptic drug treatment and fair prognosis.